THE CONSTRAINTS OF LEGAL FACTORS IN CONTROLLING ABANDONED LAND AFTER THE ENACTMENT OF THE JOB CREATION LAW - Nike Gifitriani; Emelia Kontesa; Herawan Sauni (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
Controlling abandoned land is a form of law enforcement in the context of implementing “instruction” in the Basic Agrarian Law (henceforth UUPA – Undang-Undang Pokok Agraria), and that the law functions as a social control exercised by the state against holders of land rights and Basis for Land Control (henceforth DPAT – Dasar Penguasaan Atas Tanah) that do not fulfill the obligations. Based on Article 27, Article 37, and Article 40 of the UUPA, land rights will be nullified if neglected. However, the UUPA has not explained how a land is categorized as abandoned land, and has not regulated the Control of Abandoned Land. Government Regulation No. 11 of 2010 is considered ineffective in overcoming the problem of controlling abandoned land so that it was revoked. Then, Government Regulation Number 20 of 2021 was stipulated. This law is a derivative of the Omnibus Law, and it is the basis for controlling the abandoned land. This paper aims to investigate the obstacles to controlling the abandoned land after the enactment of the Omnibus Law.